Social implications of women’s language in media discourse - Nikolić, Melina M.; Babić Antić, Jelena B. (Sociološki pregled, 2020)
This paper deals with linguistic means that characterize women’s speech in a specific type of media discourse – confrontational television interview, their meanings and social implications. The aim of this research is to examine whether linguistic patterns of women’s language in media discourse comprise the basic features of women’s language and which ones, as well as to identify their functions and social implications. The methodological framework draws on Critical Discourse Analysis and the three-dimensional model which analyses the corpus as (1) text, (2) discursive practice, and (3) social practice. The research starts with the assumption that, if the relationship between discourse and society is dialectical, i.e. discourse constitutes society, and is itself influenced by society, changes in the former inevitably cause changes in the latter. Consequently, if women’s social position is reflected in their language, and vice versa, we assume that changes in the social position of women are also reflected in the language they use. Also, by generating changes in the discourse, women can improve their position in society. The results obtained from the analysis largely confirm the initial assumption.
Keywords: linguistic means; gender studies; language and gender; critical discourse analysis; confrontational interview